Extracellular Vesicles Derived From Ex Vivo Expanded Regulatory T Cells Modulate In Vitro and In Vivo Inflammation - Thome, Aaron D.; Thonhoff, Jason R.; Zhao, Weihua; Faridar, Alireza; Wang, Jinghong; Beers, David R.; Appel, Stanley H. (Frontiers in Immunology, 2022)
Extracellular vehicles (EVs) are efficient biomarkers of disease and participate in disease pathogenesis; however, their use as clinical therapies to modify disease outcomes remains to be determined. Cell-based immune therapies, including regulatory T cells (Tregs), are currently being clinically evaluated for their usefulness in suppressing pro-inflammatory processes. The present study demonstrates that ex-vivo expanded Tregs generate a large pool of EVs that express Treg-associated markers and suppress pro-inflammatory responses in vitro and in vivo. Intravenous injection of Treg EVs into an LPS-induced mouse model of inflammation reduced peripheral pro-inflammatory transcripts and increased anti-inflammatory transcripts in myeloid cells as well as Tregs. Intranasal administration of enriched Treg EVs in this model also reduced pro-inflammatory transcripts and the associated neuroinflammatory responses. In a mouse model of amyotrophic lateral sclerosis, intranasal administration of enriched Treg EVs slowed disease progression, increased survival, and modulated inflammation within the diseased spinal cord. These findings support the therapeutic potential of expanded Treg EVs to suppress pro-inflammatory responses in human disease.